Roman Myths - Masters, Anthony (New York Peter Bedrick Books, 1999)
An illustrated collection of ten Roman myths including "The Survivors," "Romulus and Remus," "The Broken Promise," "The Battle for Rome," "The Monster Child," and "Mors."
Keywords: Mythology - Roman